Peran Badan Pengendalian Dampak Lingkungan Daerah dalam Pengendalian Pencemaran Terhadao Kegiatan Industri di Kota Batam Tahun 2011-2014 - Dian Aryadana; Wan Asrida (Nakhoda: Jurnal Ilmu Pemerintahan, 2015)
This research is intended to find out the role of the regional environmental impact Control Agency of Batam City against the environmental problems that occur in industrial areas namely, Batam city, concerning sustainable development based upon the environment, the activities of the industry now aims to build an economic sector but has a negative effect that is the pollution of the environment. In this case in Batam city frequent occurrence of environmental pollution caused by industrial activity namely with disposal of waste which are not in place. This research is focused on environmental impact Control Agency area of Batam city authorities in the control of the environment . With the outline of the research issues namely how environmental impact Control Agency the role of the Regions in the control of pollution of the environment against industrial activity in Batam city in 2011-2014 and the factors restricting the role of the regional environmental impact Control Agency in controlling environmental pollution in Batam city in 2011-2014. Type of this research is a descriptive i.e. researchers provide a description and overview of the phenomenon or social symptoms examined by independent variables described in a systematic and accurate. Method of data collection is done by means of interviews and the documentation. The results of this research show that the role of environmental impact Control Agency area of Batam city in pollution control against industrial activity carried out according to its function but have not run well in accordance with the goals and targets that have been set. This is not in accordance with the duties and functions of the regional environmental impact Control Agency of Batam city, resulting in less the maximum role of Bapedalda itself in controlling pollution that occurred in Batam city. So it should be should be able to stake Bapedalda holder which is professional in the discharge of pollution control and must be capable of tackling the obstacles faced.